The impact of maintaining corporate accounting through outsourcing from Bangladesh during this slow-paced economy - Ehsan, Khawja Shahzeer (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.